2007
DOI: 10.1111/j.1744-9987.2007.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HELP Therapy on Acute Ischemic Stroke and Vascular Endothelial Cell Function

Abstract: To evaluate the therapeutic effects of the HELP system (heparin-induced extracorporeal low-density lipoprotein-apolipoprotein(a)-fibrinogen precipitation) in patients with acute ischemic stroke and probe into its possible mechanism, 10 patients with acute ischemic stroke were included in this study and received the HELP therapy in addition to low molecular weight dextran, salvia miltiorrhiza and aspirin. Matched with gender, age, European Stroke Scale (ESS) and fibrinogen, 20 patients with cerebral infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…High CRP is associated with a more severe stroke and a higher mortality (8–10,19). Wang et al showed that HELP apheresis reduced plasma CRP by 50% in preeclamptic patients (20), and Xue et al reported a 19% reduction of CRP after treatment (21). We examined the content of CRP in brain tissues to investigate the correlation between CRP and brain damage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…High CRP is associated with a more severe stroke and a higher mortality (8–10,19). Wang et al showed that HELP apheresis reduced plasma CRP by 50% in preeclamptic patients (20), and Xue et al reported a 19% reduction of CRP after treatment (21). We examined the content of CRP in brain tissues to investigate the correlation between CRP and brain damage.…”
Section: Discussionmentioning
confidence: 97%
“…Uno and colleagues (22) reported that a persistent increase in plasma oxLDL was associated with an enlargement of the ischemic lesion in the early phase after cerebral insult. Xue et al (21) reported that HELP apheresis significantly reduced plasma oxLDL (38%), CRP (19%), and fibrinogen (55%) immediately after treatment in acute stroke patients. In our study, DELP treatment suppressed the production of oxLDL ( Fig.…”
Section: Gj Liu Et Al E152mentioning
confidence: 99%